Nuclear energy: political will most crucial - Chew, Alvin (2022)
Nuclear energy is not a nascent topic in Southeast Asia, with some countries having started their capacity building almost 50 years ago. But, why have none of the ASEAN countries adopted nuclear for electricity generation?